Comparative trial of 2 weeks and 8 weeks cyclophosphamide in steroid-sensitive relapsing nephrotic syndrome of childhood. Issue 4 (April 1973) - Barratt, T. M.; Cameron, J. S.; Chantler, C.; Ogg, C. S.; Soothill, J. F.
Abstract : A comparative trial of 2 weeks and 8 weeks cyclophosphamide therapy given during steroid-maintained remission in 32 children with steroid-sensitive relapsing nephrotic syndrome of childhood is reported. A significantly greater number of the 16 children who received 2 weeks therapy relapsed after steroid withdrawal than of those who received 8 weeks therapy. Relapses occurred later after 2 weeks cyclophosphamide therapy than in our previous experience of steroid treatment alone.